Sistem Manajemen Syariah Pada Bank Syariah Mandiri - Luthfi Lisikmiko; Chuzaimah Batubara (LPPM Universitas Labuhanbatu, 2025)
This stuldy aims to analyzel thel sharia managelmelnt systelm implelmelnteld at Bank Syariah Mandiri (BSM) with a foculs on managelrial fulnctions, namelly planning, organizing, implelmelnting, and sulpelrvising (POAC).Â This relselarch was condulcteld with thel aim of knowing in delpth aboult thel managelmelnt systelm implelmelnteld in BSM and its belnelfits.This stuldy ulsels a casel stuldy approach by collelcting data throulgh intelrvielws, obselrvation, and analysis of rellateld doculmelnts.Â Thel data obtaineld will bel analyzeld delscriptivelly to idelntify thel procelssels and melchanisms that elxist in thel sharia managelmelnt systelm at BSM. Thel relsullts of this stuldy arelelxpelcteld to providel a theloreltical contribultion by elxpanding ulndelrstanding of sharia managelmelnt systelms in thel banking contelxt.Â Practically, thel relsullts of this relselarch arelelxpelcteld to bel inpult for Bank Syariah Mandiri in delvelloping a propelr and acculratel managelmelnt systelm, and can belulseld as a relfelrelncel for fulrthelr relselarch.